Protocol for a randomised controlled trial of an outreach support program for family carers of older people discharged from hospital - Toye, Christine; Moorin, Rachael; Slatyer, S.; Aoun, Samar; Parsons, R.; Hegney, D.; Maher, S.; Hill, Keith (BioMed Central Ltd., 2015)
Background: Presentations to hospital of older people receiving family care at home incur substantial costs for patients, families, and the health care system, yet there can be positive carer outcomes when systematically assessing/addressing their support needs, and reductions in older people's returns to hospital attributed to appropriate discharge planning. This study will trial the Further Enabling Care at Home program, a 2-week telephone outreach initiative for family carers of older people returning home from hospital. Hypotheses are that the program will (a) better prepare families to sustain their caregiving role and (b) reduce patients' re-presentations/readmissions to hospital, and/or their length of stay; also that reduced health system costs attributable to the program will outweigh costs of its implementation. Methods/Design: In this randomised controlled trial, family carers of older patients aged 70+ discharged from a Medical Assessment Unit in a Western Australian tertiary hospital, plus the patients themselves, will be recruited at discharge (N = 180 dyads). Carers will be randomly assigned (block allocation, assessors blinded) to receive usual care (control) or the new program (intervention). The primary outcome is the carer's self-reported preparedness for caregiving (Preparedness for Caregiving Scale administered within 4 days of discharge, 2-3 weeks post-discharge, 6 weeks post-discharge). To detect a clinically meaningful change of two points with 80 % power, 126 carers need to complete the study. Patients' returns to hospital and subsequent length of stay will be ascertained for a minimum of 3 months after the index admission. Regression analyses will be used to determine differences in carer and patient outcomes over time associated with the group (intervention or control). Data will be analysed using an Intention to Treat approach. A qualitative exploration will examine patients' and their family carers' experiences of the new program (interviews) and explore the hospital staff's perceptions (focus groups). Process evaluation will identify barriers to, and facilitators of, program implementation. A comprehensive economic evaluation will determine cost consequences. Discussion: This study investigates a novel approach to identifying and addressing family carers' needs following discharge from hospital of the older person receiving care. If successful, the program has potential to be incorporated into routine post-discharge support. Trial registration: Australian and New Zealand Clinical Trial Registry: ACTRN12614001174673.